Digital Compensation of Relative Phase Noise for DSCM Based Coherent Transmission System Using Forward Pumped Distributed Raman Amplification - Govind Vedala; Youichi Akasaka; Tadashi Ikeuchi; Rongqing Hui (IEEE Photonics Journal, 2019)
We experimentally demonstrate pilot aided compensation of relative phase noise (RPN) in a distributed Raman amplified coherent fiber optic system with forward pumping. This technique effectively eliminates the error floor that arises when conventional phase noise compensation algorithms track RPN, especially in the context of higher order modulation formats and low baud rate signals. Extrapolating the experimental results, we also demonstrate through measurement and simulation, the effectiveness of pilot aided RPN compensation in a 25 Gbaud, 16-QAM modulated digital-subcarrier system with 2.5 Gbaud and 5 Gbaud subcarriers.